Comparative study of torque expression among active and passive self-ligating and conventional brackets - Érika Mendonça Fernandes Franco; Fabrício Pinelli Valarelli; João Batista Fernandes; Rodrigo Hermont Cançado; Karina Maria Salvatore de Freitas (Dental Press Editora, 2015)
Abstract Objective: The aim of this study was to compare torque expression in active and passive self-ligating and conventional brackets. Methods: A total of 300 segments of stainless steel wire 0.019 x 0.025-in and six different brands of brackets (Damon 3MX, Portia, In-Ovation R, Bioquick, Roth SLI and Roth Max) were used. Torque moments were measured at 12°, 24°, 36° and 48°, using a wire torsion device associated with a universal testing machine. The data obtained were compared by analysis of variance followed by Tukey test for multiple comparisons. Regression analysis was performed by the least-squares method to generate the mathematical equation of the optimal curve for each brand of bracket. Results: Statistically significant differences were observed in the expression of torque among all evaluated bracket brands in all evaluated torsions (p < 0.05). It was found that Bioquick presented the lowest torque expression in all tested torsions; in contrast, Damon 3MX bracket presented the highest torque expression up to 36° torsion. Conclusions: The connection system between wire/bracket (active, passive self-ligating or conventional with elastic ligature) seems not to interfere in the final torque expression, the latter being probably dependent on the interaction between the wire and the bracket chosen for orthodontic mechanics.